The Role of Workplace Ostracism to Work Stress in Employees Generation Z - Widiyawati, Valentina Tyas; Prima, Ismoro Reza; Zamralita (Psyche 165 Journal, 2025)
Generation Z now entering the world of work own expectation tall to environment inclusive and collaborative work. However, the reality on the ground Work No always in accordance with hope this, especially when employee experience exclusion social. Workplace ostracism is phenomena that occur when individual feel ignored or isolated by colleagues work, which can impact negative on well-being psychological and performance they. Exclusion This often marked​ with avoidance interaction, attitude No friendly, and lack of support social, which can hinder function social employees and reduce trust​ self. Condition This become challenge Serious for Generation Z, which is known more prone to to stress and issues mental health compared generation previously. Research This aim For understand connection between workplace ostracism and stress work on employees Generation Z. Study This involving 247 employees Generation Z from various selected sectors​ through convenience sampling method ensure data diversity. Measurement variables done with Workplace Ostracism Scale (WOS) and Job Stress Scale (JSS), provisional data analysis using Pearson correlation and linear regression for identify connection between isolation in place work and level stress work. Research results show that workplace ostracism own connection significant positive​ with stress work, where exclusion be one of factor main thing that improves level stress employees. Besides that, found existence difference significant in level stress based on length of service and sector business. Based on findings this research​ This recommend intervention strategies like training interpersonal skills, management programs stress, as well as development culture more work​ inclusive use increase welfare employees and productivity organization in a way overall.